A bifunctional NiCo2S4/reduced graphene oxide@polyaniline nanocomposite as a highly-efficient electrode for glucose and rutin detection. (9th May 2018) - Wang, Yanying; Zhong, Ji; Ding, Fang; Zhao, Qingbiao; Zhang, Zhaoyi; Liu, Xin; Liu, Yiting; Rao, Hanbing; Zou, Ping; Wang, Xianxiang
Abstract : A novel NiCo2 S4 /reduced graphene oxide@polyaniline (NiCo2 S4 /rGO@PANI) composite was synthesized by a facile two-step hydrothermal treatment and calcination, which was coupled with an in situ polymerization process. Abstract : A novel NiCo2 S4 /reduced graphene oxide@polyaniline (NiCo2 S4 /rGO@PANI) composite was synthesized by a facile two-step hydrothermal treatment and calcination, which was coupled with an in situ polymerization process. A bifunctional electrochemical sensor was developed for glucose electrocatalysis and rutin oxidation based on this composite modified glassy carbon electrode (GCE). The as-prepared composite was characterized by transmission electron microscopy (TEM), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), electrochemical impedance spectroscopy (EIS), thermogravimetric analysis (TGA), and Fourier transform infrared spectroscopy (FT-IR). Furthermore, the NiCo2 S4 /rGO@PANI/GCE composite displayed excellent electrocatalytic activity towards glucose in the linear range of 1–7000 μM and a detection limit of 0.14 μM (S/N = 3). And for rutin, the linear range was 0.01–200 μM with a low detection limit of 0.007 μM (S/N = 3). The sensitivity of this sensor for glucose and rutin was evaluated to be 4.924 and 75.50 μA μM −1 cm −2, respectively. In addition, this sensor delivered high selectivity, good reproducibility, and long-term stability. The modified electrode was also employed to determine glucose in human blood serum samples and rutin in orange juice, buckwheat tea, and compound rutin tablet samples.